Analisis Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Widyastuti, Lisa Asih (2016)
The purpose of this research is to find out empirical evidence and analyze the effect of financial performance to the value of the firm (study empirical is manufacturing companies listed in Indonesia Stock Exchange) show that simultaneously and partially. Sampling method that is used is purposive sampling and there are 71 sample companies that will be research objects. Analytical techniques used in this research is multiple linear regression analysis by using SPSS where the data was tested using the coefficient of determination, test F, t test of the significant level is 5%. Furthermore the data was tested using the classical assumptions in terms of The independence variables in this research are financial performance in terms of normality test, multikolinearitas test and heterokedastisitas test. Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Growth in Earnings After Tax (GEAT), while the value of the firm as dependent variable. The results of this research show that simultaneously, all of independent variables have significant effect to the value of the firm. Partially, Return On Assets (ROA) and Return On Equity (ROE) had positive effect and significant to the value of the firm (MBV), while Net Profit Margin (NPM), Debt to Equity Ratio (DER) and Growth in Earnings After Tax (GEAT) had negative effect and not significant to the value of the firm (MBV).